1970
DOI: 10.1080/10862967009546947
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Patterns in Elemental Skills: Knowledge of Upper-Case and Lower-Case Letter Names

Abstract: Two hundred children in grades K-3 were administered a test designed to assess knowledge of letter names in both upper-and lowercase primary type. Children exhibited better knowledge of upper-than lowercase letter names. Rank order, correlational analyses performed to determine the relationship of letter naming to visual discrimination and letter frequency revealed different patterns for upper-and lowercase letters. A subsequent, factor analytic treatment of the data also suggested differences in upper-and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

1972
1972
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 4 publications
0
14
0
2
Order By: Relevance
“…Central among these emergent literacy skills are the three areas of alphabet knowledge, phonological awareness, and oral language (Storch & Whitehurst, 2002; Whitehurst & Lonigan, 1998; Lonigan, Schatschneider, Westberg & the National Early Literacy Panel, 2008a). The robust and unique predictive validity of these three skill sets has been repeatedly demonstrated in a wide array of studies with varied assessment measures (Catts, Fey, Zhang, & Tomblin, 1999; deJong & van der Leij, 1999; Naslund & Schneider, 1996; Scarborough, 1989; 1998; Wagner, Torgesen, & Rashotte, 1994; Wagner et al, 1997), including both norm-referenced standardized assessments and researcher-developed measures. Further, there is increasing evidence that all three are causally related to decoding, spelling, or comprehension skill, perhaps especially when instruction combines a focus on more than one of these elements (Lonigan, Schatschneider, Westberg & the National Early Literacy Panel,2008b; Schneider, Roth, & Ennemoser, 2000; Share & Gur, 1999).…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Central among these emergent literacy skills are the three areas of alphabet knowledge, phonological awareness, and oral language (Storch & Whitehurst, 2002; Whitehurst & Lonigan, 1998; Lonigan, Schatschneider, Westberg & the National Early Literacy Panel, 2008a). The robust and unique predictive validity of these three skill sets has been repeatedly demonstrated in a wide array of studies with varied assessment measures (Catts, Fey, Zhang, & Tomblin, 1999; deJong & van der Leij, 1999; Naslund & Schneider, 1996; Scarborough, 1989; 1998; Wagner, Torgesen, & Rashotte, 1994; Wagner et al, 1997), including both norm-referenced standardized assessments and researcher-developed measures. Further, there is increasing evidence that all three are causally related to decoding, spelling, or comprehension skill, perhaps especially when instruction combines a focus on more than one of these elements (Lonigan, Schatschneider, Westberg & the National Early Literacy Panel,2008b; Schneider, Roth, & Ennemoser, 2000; Share & Gur, 1999).…”
mentioning
confidence: 84%
“…Studies spanning several decades of research indicate that similarity in the shape of letters can lead to children's difficulties in discrimination and recall of letter names, perhaps particularly with lower case letter presentations (e.g., b and d; p and q) (Courrieu & de Falco, 1989; Gibson, Gibson, Pick & Osser, 1962; Goikoetxea, 2006; Lahey & McNees, 1975; Smythe Stennet, Hardy, & Wilson, 1970; Treiman et al, 2006). Treiman and Kessler (2003) also found that letters that share phonemes in their names with many other letters may be more readily confused; Treiman et al (2006) extended this finding for English and Portuguese to include an interaction between visual and phonological similarity.…”
Section: Letter-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This knowledge seems to be universally the same for children of preschool age, regardless of their native language (Evans et al, 2006;McCormick & Mason, 1986;Smythe, Stennett, Hardy, & Wilson, 1971). This might be due to the greater visual distinctiveness of uppercase letters in all alphabets, and the more frequent appearance of these letters in bold type in children's books, titles, labels and names.…”
Section: Uppercase and Lowercase Letter Knowledgementioning
confidence: 96%
“…Ranks 6 and 7 give the order in which seven-year-olds (Smythe, 1971) and first graders (Durrell, 1956) learn to correctly name the lower-case consonant letters. Rank 8 indicates the rank order in which preschool children learn to pronounce sounds when shown letters (Coleman, 1970).…”
Section: Determining a Better Sequencementioning
confidence: 99%